Status signaling products - what it means to women. - Chui, C.T.B. (Malaysian Consumer and Family Economics Association, 2010)
An emerging phenomenon in the global consumer culture is the rising trend of discretionary income expended on status products. Yet status is the least recognised justifier for discretionary purchases. Few consumers are willing to own up to status as important in making discretionary purchase decisions (Danziger, 2004). Malaysians were found to spend a larger proportion of their personal annual income on discretionary items such as personal travel, entertainment, fashion, holiday vacation and dining compared to its neighboring ASEAN countries (Azizan, 2008). This trend of status consumption is prominent in the female market. Total discretionary spending by women in Asia Pacific was estimated at US$386 billion in 2004 and expected to rise to US$516 billion by 2014 (Goh, 2006). This paper reports the preliminary results of a larger study on what constitute status signaling products and what it means to women. It explores 14 items commonly purchased by women and thought to convey status. The study utilises survey approach to a convenient sample of 89 Malaysian and Iranian women. Respondents were asked whether the purchase of selected products/services could form an impression of that person, how much discretionary spending power one has and whether it tells about the individual's social status. Findings indicate Malaysian females place more emphasis on status consumption of products such as business suit, vacation at a hotel resort, jewelry, beauty services and PDA whilst Iranians ranked university education as status-conveying, followed by business suit, holiday at a hotel resort, dress shoes and PDA. Products that form an impression about an individual were almost similar between the two groups. Spending on vacation to a hotel resort, jewelry, business suit and PDA reflected their discretionary income power for both groups. Products that portray strong social status between Malaysians and Iranians differed widely. Findings suggest that women acquire status through their possessions and take self-identity from their possessions. The study has implications for marketers targeting the female market segment for status products and consumers' control on discretionary spending.